Étude des discours d`entraîneurs professionnels durant une rencontre de Handball selon la perspective du « Coaching Model » - Debanne, T.; Fontayne, P. (Science et motricité, 2012)
The aim of this study is to describe and analyze the communication of professional coaches to their male handball teams according to the different levels of play between competing teams. Content derived from coaches` communications was analyzed using both deductive and inductive approaches according to the Coaching Model perspective proposed by Côté, J., Salmela, J.H., Trudel, P., Baria, A., & Russel, S. (1995) (The Coaching Model: A grounded assessment of expert gymnastic coaches` knowledge. Journal of Sport & Exercise Psychology, 17, 1-17). Results show that coaches mainly address the physical and mental commitment of their players when facing a comparatively competitive opponent. When disparity exists between opponents, however, there is more emphasis on goal attainment than overall team performance. More generally, results confirm that management of the players` physical and mental commitment and global and inter-individual balance of power are the coaches` main preoccupations during a game.